Common Good at the beginnings of the Society of Jesus: from the first years to the ideas of Francisco Suárez - Sepúlveda-del-Río, Ignacio (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Jesuits have been accused, many times, of being a hybrid order: they are religious and secular at the same time, they are concern about the Gospel and also about economics, politics, science, etc. Where does this way to be come from? We think that the key to answer to this question lays on the Jesuit concern for the common good. This very idea is to be found in their foundational documents.
Keywords: jesuits; common good; Francisco Suárez